Remark on the Second Bounded Cohomology of Amalgamated Product of Groups - Faĭziev, Valeriy A.; Sahoo, Prasanna K. (Sarajevo Journal of Mathematics, 2024)
For any cardinal number ${\mathcal M}$ we construct examples of amalgamated products and HNN extensions of groups such that the dimension of the space of second bounded cohomologies is at least ${\mathcal M}$. Also we describe the space of pseudocharacters of the group $GL(2,F_2[z]).$ 2000 Mathematics Subject Classification. Primary: 20M15, 20M30, 39B82